STUDY OF PROFESSIONAL COMPETENCE IN FUTURE MILITARY SERVANTS IN SOCIAL-PSYCHOLOGICAL RESEARCH - Abralova Zabarjat Djuraevna; Ulkhudjayev Rasul Zarif ugli (Academia Science Repository, 2023)
The article provides scientific information, instructions and recommendations based on statistical, analytical and bibliographic methodology about the factors of formation of professional competence of future military soldiers and the study of this issue in socio-psychological research.